Construct validity of gymnastics-specific assessment on the neuromuscular function of shoulder flexor and extensor muscles - Milosis, D. C.; Siatras, T. A.; Christoulas, K. I.; Patikas, D. A. (Sports Biomechanics, 2020)
The present study examined the construct validity of gymnastics-specific measurements of the shoulder flexor and extensor neuromuscular function. Fifteen male gymnasts and 18 male physical education (PE) students participated voluntarily. The electromyogram (EMG) of 3 flexor and 3 extensor shoulder muscles was assessed during isometric (45, 90, and 135º) and isokinetic (concentric and eccentric 60, 180, and 300º/s) shoulder flexion/extension. Peak torque (PT) and neuromuscular function in terms of neuromuscular efficiency (NME, i.e. torque to EMG ratio) and antagonist/agonist coactivation index were evaluated. The construct validity of the measurements was supported by the ability to discriminate between gymnasts and physical education (PE) students, taking into consideration the shoulders` neuromuscular function parameters (37%-57% of the variability explained). After accounting for the limitations of the study, these findings may assist gymnastics coaches and researchers to develop and evaluate more effective training methods for athletes related to shoulder joint physiological characteristics and level of expertise.